Rural–Urban Transformation and Landuse Dynamics in Gunungpati on the Northern Flank of Mt. Ungaran, Semarang, Indonesia - Juhadi Juhadi; Tjaturahono Budi Sanjoto; Elok Surya Pratiwi; Edy Trihatmoko; Istiqomah Istiqomah; Aprillia Findayani (Faculty of Geography, Universitas Gadjah Mada, 2021)
Most of the northern flank of Mt. Ungaran is subject to intensive land occupation that makes landuse change inevitable. The research objectives of this study were to examine the spatial patterns of land-use dynamics from 1997 to 2018 and to analyze their impact on the rural–urban structure of Gunungpati sub-district using on-screen digitation. Rural–urban structure was analyzed based on landuse composition by area in each village. This research revealed that forest areas and paddy fields were decreasing year by year. Over the study period of 21 years, Gunungpati experienced deforestation of 1,777 ha and increase in built-up area of 1,295 ha, forcing shifting in rural structure. Most villages that were categorized as rural frame zones in 1997 had changed into urban–rural frame zones by 2018. This situation must be controlled, since much of Gunungpati territory plays a significant role as a groundwater recharge zone for the Semarang lowland area.